Bubble Echo Chamber Effects Phenomenon in the 2024 Indonesia Regional Head Elections - Sihombing, Desi Natalia; Rahayu, Liska; KY, I Gede Sumertha; Sukendro, Achmed (The Republic of Indonesia Defense University, 2024)
The accelerating processes of globalization and democratization have transformed national security dynamics. National security encompasses a state’s capacity to defend itself against internal and external threats. The emergence of social media, driven by advancements in internet technology, plays a significant role in influencing the political landscape. However, the growing dependence on social media platforms has given rise to the phenomenon of the echo chamber effect, where individuals are increasingly exposed to content that reinforces their pre-existing beliefs, exacerbating polarization, which has the potential to heighten political tensions and trigger social fragmentation, particularly during electoral cycles. This study focuses on Indonesia’s 2024 Regional Head Elections, analyzing how the echo chamber effect may threaten national cohesion. Using a qualitative approach, data was collected through observational techniques and an extensive literature review. The study analyzes information patterns on social media, identifies emerging conflict triggers, and proposes relevant preventive measures. Key findings highlight the importance of government intervention in monitoring social media platforms and enhancing public digital literacy. The recommended strategic policies include AI-based monitoring, forming expert-led rapid response teams, and strengthening regulations to manage content exacerbating polarization. Collaboration among stakeholders, including the government, private sector, and civil society, is crucial in mitigating social fragmentation caused by information polarization. This study also advocates implementing national digital literacy initiatives to counter disinformation and polarization. Therefore, this research provides valuable insights into safeguarding national security amidst growing digital threats while supporting the sustainability of democratic processes in Indonesia.